2014
DOI: 10.1503/cjs.003513
|View full text |Cite
|
Sign up to set email alerts
|

Viability assessment of the chondral flap in patients with cam-type femoroacetabular impingement: a preliminary report

Abstract: Background: Delaminated acetabular cartilage is a common finding in patients undergoing surgical dislocation or hip arthroscopy in the treatment of cam-type femoroacetabular impingement. Current treatment involves resection of the free cartilage flap with or without acetabular rim trimming. The viability of the delaminated cartilage flap is not known. We sought to examine if the acetabular cartilage still has viable cartilage cells and, if so, what type of cartilage is present. Methods:We examined the delamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…The extent of cell viability of primary human chondrocytes derived from the damaged hip areas was comparable to that reported by other studies. For instance, Meulenkamp et al found an overall viability of ninety percent in chondrocytes derived from delaminated cartilage flaps from patients with symptomatic camtype impingement which is in line with our findings 23 . Notably transport simulation, being a crucial prerequisite for clinical translation, did not affect cell viability.…”
Section: Discussionsupporting
confidence: 92%
“…The extent of cell viability of primary human chondrocytes derived from the damaged hip areas was comparable to that reported by other studies. For instance, Meulenkamp et al found an overall viability of ninety percent in chondrocytes derived from delaminated cartilage flaps from patients with symptomatic camtype impingement which is in line with our findings 23 . Notably transport simulation, being a crucial prerequisite for clinical translation, did not affect cell viability.…”
Section: Discussionsupporting
confidence: 92%
“… 16 , 60 Unlike our study, the control samples used were animal articular cartilage and human knee cartilage, and no direct comparison of tissue viability and quality was made with the human acetabular articular cartilage surface. 16 In another study by Meulenkamp et al, 32 the reported cellular viability of 12 chondral flaps was higher, with an overall viability of 90%. This was measured from H&E-stained sections, which can overestimate viability, as suggested by the authors.…”
Section: Discussionmentioning
confidence: 95%
“…Under light microscopy a musculoskeletal pathologist assessed the cartilage viability and found more than 90% of viable chondrocytes in 11 out of 12 samples. In addition, they found that in 50% of the flaps the cartilage was predominantly hyaline [14].…”
Section: Discussionmentioning
confidence: 99%